THE INFLUENCE OF TASTE AND PRICE ON PURCHASE DECISIONS CASE STUDY OF NOMO COFFEE SHOP IN BANDUNG - Muhamad Irvan; Agis Maharani; Muhammad Nizar Dzaki (STIA Bagasasi, 2022)
The development of the coffee industry in Indonesia has increased rapidly in recent years. In the face of increasingly fierce competition, coffee shops have become one of the favorite places for people to enjoy coffee. One of the famous coffee shops in Bandung is